IMPROVED IMPLEMENTATION of THE COMMUNITY-BASED WATER SUPPLY AND SANITATION PROGRAM (PAMSIMAS) in TANGGA JAYA VILLAGE, DULUPI SUB-DISTRICT, BOALEMO DISTRICT - Kiayi, Merlis; Tui, Fenti Prihatini; Tantu, Romy (Public Policy Journal, 2024)
This study aims to determine (1) The Implementation Process of the Community-Based Drinking Water Supply and Sanitation Program (PAMSIMAS) in Tangga Jaya Village, Dulupi District, Boalemo Regency, (2) Factors that Determine the Success of the Implementation of the Community-Based Drinking Water Supply and Sanitation Program (PAMSIMAS) in Tangga Jaya Village, Dulupi District, Boalemo Regency, with indicators of Communication, Resources, Disposition, and Bureaucratic Structure. This research method uses a qualitative approach with a qualitative description type of research. Based on the results of research analyzed in the field, it shows that the Implementation Process of the Community-Based Water Supply and Sanitation Program (PAMSIMAS) in Tangga Jaya Village, Dulupi Sub-district, Boalemo Regency, at the stages of Disbursement of Direct Community Assistance Funds, Implementation of Community Work Plan Activities and Completion of Activity Implementation, has generally been carried out well. The disbursement of direct assistance funds went well because 100% of the funds came from the PERKIM Office. The Implementation of Community Work Plan Activities and the Completion of Activity Implementation stages are optimal because they are in accordance with existing Pamsimas procedures and guidelines. Factors that determine the success of the Implementation of the Community-Based Drinking Water Supply and Sanitation Program (PAMSIMAS) in Tangga Jaya Village, Dulupi Sub-district, Boalemo Regency, which include Communication, Resources, Disposition and Bureaucratic Structure, have been implemented well.